Electrochemical analysis of corrosion inhibition shallot leaf (Allium cepa) extract on mild steel in acidic medium at different immersion times - Siska Prifiharni; Amalia Rizky Sabilla; Gadang Priyotomo; Arini Nikitasari; Rahayu Kusumastuti; Siti Musabikha; Rahma Nisa Hakim; Yanyan Dwiyanti; Bening Kambuna (Zaštita Materijala)
Plant derivatives as eco-friendly corrosion inhibitors are currently greatly interested in much research. Shallot leaf (Allium cepa) was utilized in 0.1M HCl as a corrosion inhibitor of mild steel. The functional groups present in the macerated extract were subsequently identified using an FTIR test. Electrochemical tests such as tafel polarization and EIS were carried out to determine the corrosion inhibition performance of shallot leaf extract on the SS400 steel. The results of the electrochemical analysis show that shallot leaf extract can inhibit mild steel up to 94% at a concentration of 500 ppm. Furthermore, the addition of SLE reduces surface damage of mild steel, which can be seen by SEM.